Hereditary haemorrhagic telangiectasia: development of a regional life-course collaborative clinical care pathway. (2nd November 2021) - Anderson, Emily; Green, Richard; Swift, Andrew; Semple, Malcolm G
Abstract : Hereditary haemorrhagic telangiectasia is a rare, genetic disorder that can present at any age. It is characterised by epistaxis, mucocutaneous telangiectasia and visceral arteriovenous malformations, which can affect multiple organs. Early diagnosis and management reduces the morbidity and mortality associated with the disease. There is a well-established hereditary haemorrhagic telangiectasia clinic in London, and excellent links across Europe via the European Reference Network. However, local coordinated care for patients with hereditary haemorrhagic telangiectasia across the UK can be variable and often absent for children and young people. Some patients travel long distances to receive care in London, while others are referred to local clinicians or lost to follow up entirely. This article presents the experience to date from two regional UK centres (Liverpool and Dundee) where care for patients with hereditary haemorrhagic telangiectasia is being coordinated and streamlined. While there is still a lot to learn, this article highlights some of the successes and challenges identified so far, with suggestions for how these could be addressed. Collaborative regional networks such as these can facilitate the sharing of best practice and ensure that all patients with hereditary haemorrhagic telangiectasia are able to access safe, high-quality care.